Methylated B3GAT2 and ZNF793 are potential detection biomarkers for Barrett’s esophagus - Yu, Ming (Cancer Epidemiol Biomarkers Prev, 2015)
BACKGROUND: Barrett’s esophagus (BE) is a pre-neoplastic condition in which normal esophageal squamous epithelium (SQ) is replaced by specialized intestinal metaplasia. It is the presumed precursor for esophageal adenocarcinoma (EAC) as well as the strongest risk factor for this cancer. Unfortunately, many patients with BE go undiagnosed under the current BE screening guidelines. The development of noninvasive and accurate BE detection assays could potentially identify many of these undiagnosed BE patients. METHODS: DNA methylation is a common epigenetic alteration in BE. Therefore, we conducted a genome-wide methylation screen to identify potential BE biomarkers. Samples from SQ (N=12), stomach (N=28), and BE (N=29) were analyzed and methylation levels at over 485,000 CpG sites were compared. Pyrosequencing assays were used to validate the results and MethyLight assays were developed to detect the methylated alleles in endoscopic brushings. RESULTS: We discovered two genes, B3GAT2 and ZNF793, that are aberrantly methylated in BE. Clinical validation studies confirmed B3GAT2 and ZNF793 methylation levels were significantly higher in BE samples (median = 32.5% and 33.1%, respectively) than in control tissues (median = 2.29% and 2.52% respectively; P < 0.0001 for both genes). Furthermore, gene specific MethyLight assays could accurately detect BE (P < 0.0001 for both) in endoscopic brushing samples. CONCLUSION: B3GAT2 and ZNF793 are hypermethylated in BE, and the methylation status of these genes can be used to detect BE in tissue samples. IMPACT: These findings support the development of methylated B3GAT2 and ZNF793 as biomarkers for noninvasive assays for the detection of BE.